Memes As a Symbol Of Political Communication - Fajar Dwi Putra; Hafied Cangara; Hasrullah Hasrullah (Universitas Ahmad Dahlan, 2022)
Memes as a culture of political consumerism restructure the position of communication in society, shrink traditional forms of political communication and cause ideological loyalty to erode deeper. The study used a qualitative design to explain forms of political propaganda communication as a means of communicating. The method used is a critical analysis of the contents of Grant Kien's book entitled Communicating with Memes Consequences in Post-truth Civilization. The results generally explain that Grant Kien's book Communicating with Memes Consequences in Post-truth Civilizationprovides a balanced analysis of the purpose of memes, identity politics, and reconstruction of Political communication in the post-truth era. In the early chapters, Grant Kien gave assumptions about the chaos of communication posted on social media called Digital Steamworks. In his writing, Kien said that memes on social media are a tool of political propaganda and a means to corner the position of the media and society. The political styles highlighted on social media are increasingly operating as a focus for post-truth lifestyle choices rooted in identity politics. Political deconstruction became one of the conservative options, supporting a more eclectic, fluid, and specific form of political recognition. Meanwhile, memes tend to be a means of reproducing political messages and propaganda in a narrower spectrum. The study concludes that memes, which were initially a form of the general message of communication, shifted into a tool of political propaganda.